Strong Electro‐Optic Effect and Spontaneous Domain Formation in Self‐Assembled Peptide Structures. Issue 9 (11th May 2017) - Gilboa, Barak; Lafargue, Clément; Handelman, Amir; Shimon, Linda J. W.; Rosenman, Gil; Zyss, Joseph; Ellenbogen, Tal
Abstract : Short peptides made from repeating units of phenylalanine self‐assemble into a remarkable variety of micro‐ and nanostructures including tubes, tapes, spheres, and fibrils. These bio‐organic structures are found to possess striking mechanical, electrical, and optical properties, which are rarely seen in organic materials, and are therefore shown useful for diverse applications including regenerative medicine, targeted drug delivery, and biocompatible fluorescent probes. Consequently, finding new optical properties in these materials can significantly advance their practical use, for example, by allowing new ways to visualize, manipulate, and utilize them in new, in vivo, sensing applications. Here, by leveraging a unique electro‐optic phase microscopy technique, combined with traditional structural analysis, it is measured in di‐ and triphenylalanine peptide structures a surprisingly large electro‐optic response of the same order as the best performing inorganic crystals. In addition, spontaneous domain formation is observed in triphenylalanine tapes, and the origin of their electro‐optic activity is unveiled to be related to a porous triclinic structure, with extensive antiparallel beta‐sheet arrangement. The strong electro‐optic response of these porous peptide structures with the capability of hosting guest molecules opens the door to create new biocompatible, environmental friendly functional materials for electro‐optic applications, including biomedical imaging, sensing, and optical manipulation. Abstract : Di‐ and triphenylalanine self‐assembled structures demonstrate a strong linear electro‐optic effect when viewed under a unique electro‐optic microscope. Their electro‐optic coefficients are found and traced back to their structural origin. Their porous structure allows for the introduction of guest molecules for the creation of new functional electro‐optic materials for biomedical imaging, sensing, and optical manipulation.